The analysis of corrosion performance of car bodies coated by no nickel and low nickel zinc phosphating processes - Derun, EM; Demirozu, T; Piskin, MB; Piskin, S (WILEY-V C H VERLAG GMBH, 2005)
In today's automotive industry in order to protect car bodies from corrosion, spray or immersion type zinc phosphating processes are applied. In both types, nickel and chromium are widely used though they are harmful to human health and environment. In this study, car body's corrosion performance, coated by no nickel (0 ppm) and low nickel (100, 200, 300 ppm) immersion type zinc phosphating (without chromium passivation) processes, are compared to the bodies that are coated by spray and immersion type processes including nickel (500-700 ppm) and chromium. After analyzing coating weight, composition, morphology of the crystals and salt spray test corrosion performance of car bodies specimens coated by no nickel and low nickel processes are as good as the ones coated by spray and immersion phosphating processes including nickel and chromium. In developing environment consciousness, it is inevitable to favor no nickel or low nickel processes since they give no harm to nature and human health.
Keywords: Materials Science; Metallurgy & Metallurgical Engineering